Evaluation of mtDNA analysis as a screening method prior to individual identification by short tandem repeat analysis of sika deer (Cervus nippon) for illegal disposal of hunting in Japan - Tanaka, Aki; Ueda, Reina; Udagawa, Chihiro; Omi, Toshinori; Kihara, Yuko; Hayama, Shin-ichi (Frontiers in Veterinary Science, 2025)
The sika deer (Cervus nippon) is subject to controlled abatements Japan, and in many areas hunters are subsidized by submitting tails from the dead deer. The carcasses must be properly disposed of after the tails are removed, and abandoning culled animals in the field is strictly prohibited by law. However, it has become an increasing legal problem that carcasses are left behind without proper disposal. In such cases, individual identification by DNA analysis has been considered useful to identify the culled animals and the suspects who abandoned the carcasses, and to provide scientific evidence for criminal investigations. In this study, the mtDNA D-loop region was analyzed in Sika deer using 285 deer samples with the aim of evaluating the capability of mtDNA markers as a screening method prior to performing individual identification by short tandem repeat analysis. Haplotype data obtained from 283 samples, excluding those with confirmed heteroplasmy, were used to calculate probability of random match, power to exclude, and genetic diversity. Twenty-three haplotypes were detected in 285 Japanese deer from the same local population, with mutations in the tandem repeat sequence and 48 different sites. The exclusion probability was 79.9%. The results suggested that mtDNA analysis provided moderate identification capability for screening. mtDNA analysis has proven to be a useful robust analysis in wildlife forensics when the samples were decayed and there were time and resource limitations, and is expected to be applied to solve illegal disposal of animal carcasses.